1998
DOI: 10.1111/j.1399-0039.1998.tb02277.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA polymorphisms in Italian bone marrow donors: a regional analysis

Abstract: The aim of this study was to analyse the genetic structure of the Italian bone marrow donor population on the basis of HLA polymorphisms. Maximum likelihood estimates of gene and haplotype frequencies, goodness of fit to Hardy-Weinberg predictions and heterozygosity were calculated for 18 Italian administrative regions. Moreover, the phenotypic peculiarity of the regional populations was assessed by analysing the number of "typical phenotypes" found in each region. Multivariate analyses carried out on HLA-A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 16 publications
(5 reference statements)
12
50
1
1
Order By: Relevance
“…Transposed in a larger context (i.e. in the total peninsula), these findings perfectly matched with those of an Italian study (Rendine et al 1998), confirming that HLA-A2,B51 is a Northern Italian haplotype and HLA-A24,B35 a Southern one. The immigration of Southern people is prevailingly concentrated in Milano City and its neighborhood (i.e.…”
Section: supporting
confidence: 78%
See 1 more Smart Citation
“…Transposed in a larger context (i.e. in the total peninsula), these findings perfectly matched with those of an Italian study (Rendine et al 1998), confirming that HLA-A2,B51 is a Northern Italian haplotype and HLA-A24,B35 a Southern one. The immigration of Southern people is prevailingly concentrated in Milano City and its neighborhood (i.e.…”
Section: supporting
confidence: 78%
“…Analysis of Hardy-Weinberg (HW) equilibrium suggested that the reservoirs of Pavia, Brescia and Cremona, that are in equilibrium, were composed principally by autochthonous people, while Milano and Bergamo, which deviated from HW for all the three HLA loci, revealed a more important population admixture (Table 4). This is probably due to the high rate of immigration from the other Italian regions, as reported elsewhere (Rendine et al 1998).…”
Section: mentioning
confidence: 60%
“…The analysis of HLA-DQA1 and -DQB1 polymorphisms at genomic levels was performed by the polymerase chain reaction/sequence-specific primers technique (24). The results were compared with those of 40,071 Italian bone marrow Incidental hyperglycemia in children donors enrolled in the Italian Bone Marrow Donor Registry and representative of the Italian population (25). Mean age of control subjects was 26 years and the male-to-female sex ratio was 0.98.…”
Section: Ogttmentioning
confidence: 99%
“…Many published estimates of frequency distributions of common HLA haplotype distributions for narrowlydefined national and regional populations throughout the world are available. Examples include [33], [8], [30], [34] and [10]). These estimates are usually based on samples of a few hundred individuals and hence provide reliable information only about the distributions of the most common haplotypes.…”
Section: Racial Categories and Hla Matchingmentioning
confidence: 99%